Perceptions of Effective TEFL Instructors’ Qualities: A Survey of Cambodian University TEFL Instructors - Vanna Nourn (MASI Mandiri Edukasi, 2023)
In Cambodia, English is adopted as a medium of instruction and a major subject at universities, but teaching English can be a challenge in Cambodia as most learners are not proficient. Some English classes are taught by fresh graduates with less teaching experience while, even seriously, some instructors teach subjects beyond their field, leading to poor learning. As instructors’ qualities are generally key to effective teaching and learning, this study surveyed 30 TEFL instructors at three universities in Phnom Penh. The study used a Google form to collect instructors’ perceptions of five main domains: instructors’ qualifications, content knowledge, pedagogical knowledge, pedagogical skills, and personal and interpersonal characteristics. The findings reveal higher mean scores for almost all items and overall mean scores for each domain. The results indicate that the instructors positively perceived these qualities of effective TEFL instructors. The findings can be employed as criteria for TEFL instructors and can inform universities to develop human resources with these aspects or elements when selecting English instructors. Therefore, such criteria can ensure the recruitment of TEFL instructors while TEFL instructors must improve themselves to have these qualities and other attributes for their practical teaching.